Vorasidenib- A Paradigm Shift in IDH1- or IDH2-Mutant Low-Grade Glioma Treatment - Hurais Malik; Muhammad Hudaib; Abdul Rehman (Journal of the Pakistan Medical Association)
Low-grade gliomas (LGGs) pose significant challenges in cancer research and treatment due to their infiltrative nature and tendency for recurrence, making them the most common brain tumour in adults. Most of the LGGs have the propensity to cause notable alterations in the microenvironment of the tumour thus making them difficult to treat. These alterations can be attributed to the prevalent mutations in the genes that produce isocitrate dehydrogenase (IDH) enzymes, especially in grade 2 diffuse gliomas. [1] Despite its inability to provide a complete cure, chemoradiation has been adopted as the standard therapy in grade 3 gliomas since it can lead to long-lasting remission. Chemoradiotherapy, when administered promptly, can help prevent tumour progression, and recurrence after surgery and improve long-term outcomes. Nevertheless, immediate adjuvant chemoradiotherapy is not administered in patients afflicted with tumours containing IDH mutant grade 2 gliomas. This decision is often made to circumvent potential harm such as radiation-induced cognitive problems, chemotherapy-related DNA mutations, and other negative effects on their health. [2] Due to the intricacies associated with the treatment decisions and the inclination to delay aggressive therapies to avoid adverse events, creates a necessity for a novel therapeutic strategy that is both effective and well tolerated.